AN ANALYSIS OF FIGURATIVE LANGUAGE IN THE PICTURE OF DORIAN GRAY BY OSCAR WILDE - Santoso, Muhammad Rochmat Muchson; Iskandar, Iskandar (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
Figurative language is described as the use of words or idioms having meanings that deviate from their literal meanings. Poets use this language to state things in an unconventional way, i.e. to communicate meaning indirectly. Using the theories of Knickerbocker and Reninger, In written texts, and use of figures of speech is common. . designed to achieve aesthetic effects or beauty in order to pique the reader's attention. Because figurative language is concerned with and has an aesthetic meaning, linguistic study on figurative language is interesting. The study's initial purpose was to identify the many sorts of metaphorical language that may be found in Oscar Wilde's work